Interleaved DC-DC Converter Based BL Buck Boost Converter Fed BLDC Drive - Prakash, Ch. S. V.; Kalyani, K.; Prasad, B. Sankara (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
In this paper an improved BL Buck-Boost PFC converter fed brushless direct current (BLDC) motor drive for desired speed applications has been presented. The additional inductance and power semiconductor switches gives the advantages over the conventional circuit configuration. The reliability of the circuit gets improved by proposed model. Voltage source inverter (VSI) is used to reduce the losses across the power switches. The performance of the proposed BLDC motor is evaluated over a wide range of speed control and observed in MATLAB/Simulation environment.